Assessing and Pricing Islamic Sukuk: An Overview - Muhammad Saeed Iqbal; Sofi Mohd Fikri (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2024)
Introduction to The Problem: The Islamic Sukuk conforms to Shariah guidelines. As a result, Islamic Sukuk are appealing pricing vehicles for Islamic financial institutions, Shariah-governed reserves, and Takaful Islamic insurance companies which are prohibited from investing in conventional insurance policies which provide interest or riba. Purpose/Objective Study: a growing number of Muslims with substantial net worth believe that their real estate should be in accordance with Shariah. This paper describes and explains the tools used for evaluating and assessing Islamic Sukuks. Design/Methodology/Approach: Islamic Sukuks are a type of financial instrument that follows Islamic laws, such as prohibitions against interest and gambling. These instruments are used to determine the value of real estate to ensure they meet certain Shariah requirements. The tools used for evaluating and assessing Islamic Sukuks include Islamic law, financial analysis, and real estate valuation. Findings: In the Islamic Sukuk study, an outstanding finding was the recognition of the significance of Islamic Sukuk estimation and assessment. It is expected that this study will help fill a gap in existing guidelines for Islamic Sukuk literature. Additionally, both professionals and academics will benefit from this study. The findings could provide some ideas regarding the implementation of the strategy (Shariah boards, CEOs of Islamic financial institutions). Paper Type: Research Article Keywords: Islamic Sukuk; Shariah; Assessing; Pricing; KIBOR.